Effectiveness of a portfolio model on the performance of the virtual osce - Díaz-Plasencia, Juan A.; Valencia-Mariñas, Hugo D.; Díaz-Rodríguez, Vanessa M. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
We evaluated the effectiveness of the portfolio combined with the flipped classroom, team-based learning, and online videos on students' performance in a virtual OSCE and their perception of the attributes of the OSCE and videos. The integration of the virtual OSCE in a medicine program manages the need to be on campus in the context of COVID-19, requires minimal technological resources, fulfills the main objective of creating a format of acceptable, low cost, and low administrative burden, and can be implemented in a short period.